Investigating Salespeople’s Performance and Opportunistic Behavior: Adaptive and Customer-Oriented Responses - Chankoo Yeo; Ihsan Ullah Jan (Behavioral Sciences, 2022)
This study investigates the role of value congruence and top management support on salespeople’s customer-oriented selling behavior and adaptive selling behavior. Moreover, this study has also explored the effects of salespeople’s customer-oriented selling behavior and adaptive selling behavior on sales performance and opportunistic behaviors, respectively. An online survey was administered to collect the data from salespeople in South Korea, and a total of 204 responses were undergone for formal analysis. Partial least squares structural equation modeling (PLS-SEM) was conducted to test the proposed hypotheses. The results showed that salespeople’s value congruence has a significant positive effect on customer-oriented selling behavior and top management support has a significant positive effect on salespeople’s adaptive selling behavior. The salespeople’s customer-oriented selling behavior has a significant positive effect on sales performance and a significant negative effect on opportunistic behavior. Similarly, salespeople’s adaptive selling behavior has significant positive effects on sales performance and opportunistic behaviors. Based on these findings, the implications for theory and practice are discussed in detail.